Newly Developed MAGIC Population Allows Identification of Strong Associations and Candidate Genes for Anthocyanin Pigmentation in Eggplant - Mangino, Giulio; Arrones, Andrea; Plazas, Mariola; Pook, Torsten; Prohens, Jaime; Gramazio, Pietro; Vilanova, Santiago (Frontiers in Plant Science, 2022)
MAGIC populations facilitate the genetic dissection of complex quantitative traits in plants and are valuable breeding materials. We report the development of the first eggplant MAGIC population (S3MEGGIC; 8-way), constituted by 420 S3 individuals developed from the intercrossing of seven cultivated eggplant (Solanum melongena) and one wild relative (S. incanum) parents. The S3MEGGIC recombinant population was genotyped with the eggplant 5k probes SPET platform and phenotyped for anthocyanins presence in vegetative plant tissues (PA) and fruit epidermis (FA), and for the light-sensitive anthocyanic pigmentation under the calyx (PUC). The 7,724 filtered high-confidence SNPs confirmed a low residual heterozygosity (6.87%) and a lack of genetic structure in the S3MEGGIC population, including no differentiation among subpopulations carrying cultivated or wild cytoplasm. Inference of haplotype blocks of the nuclear genome revealed an unbalanced representation of founder genomes, suggesting cryptic selection in favour or against specific parental genomes. GWAS analysis for PA, FA and PUC detected strong associations with two MYB genes similar to MYB113 involved in the anthocyanin biosynthesis pathway and with a COP1 gene, which encodes for a photo-regulatory protein and may be responsible for the PUC phenotype. Evidence was found of a duplication of an ancestral MYB113 gene with a translocation from chromosome 10 to chromosome 1. Parental genotypes for the three genes were in agreement with the candidate genes identification performed in the S3MEGGIC population. Our new eggplant MAGIC population is the largest recombinant population in eggplant and is a powerful tool for eggplant genetics and breeding studies.